#### Question

Integrate the functions `(x^2 + x + 1)/((x + 1)^2 (x + 2))`

#### Solution

Equating the coefficients of *x*^{2}, *x*,and constant term, we obtain

*A* + *C* = 1

3*A* + *B* + 2*C *= 1

2*A* + 2*B* + *C* = 1

On solving these equations, we obtain

*A* = −2, *B* = 1, and *C* = 3

From equation (1), we obtain

Is there an error in this question or solution?

Solution Integrate the Functions (X^2 + X + 1)/((X + 1)^2 (X + 2)) Concept: Integration as an Inverse Process of Differentiation.